L’influence de la religion sur la societe, d’apres things fall apart de Chinua Achebe et les soleils des_independanuiss D’ahmadou Kourouma. - Saeed, Osman (2011)
A thesis submitted to the KNUST School of Postgraduate Studies in partial fulfilment of the requirements for the degree of Master of Arts in Comparative Literature.